Evaluating the Anti-Arthritic Potential of Nerolidol Using In-Vitro and In-Vivo Models - Akhter, Shanila; Irfan, Hafiz Muhammad; Nafisa, Asma; Mustafa, Zaid; Khayam, Asma Umar; Munir, Attiya (Journal of Rawalpindi Medical College, 2025)
Objective: The current study’s objective was to assess nerolidol’s anti-arthritic effects by using both in vitro and in vivo animal models. Methods: In vitro methods included the denaturation of the egg albumin protein, bovine serum, as well as the human red blood cell membrane stabilisation assay at concentrations of 50, 100, 200, 400, 800, 1600, 3200, and 6400 μg/ml. The in vivo method involved the induction of non-immunological arthritis by formaldehyde at doses of 200, 400, and 800 mg/kg. Results: Nerolidol inhibited the denaturation of protein and neutralised the human red blood cell membrane in a concentration-dependent manner, with maximum consequence attained at 6400ug/ml ( ). Likewise, formaldehyde induced model reduced the paw volume and an extreme reduction was obtained at 800mg/kg (p ). Conclusion: These findings form a base to conclude that nerolidol supports the folklore claim of providing fortification against arthritis. Keywords: Arthritis, Nerolidol, in vitro, in vivo, protein denaturation